Work-Life Balance and Self-Efficacy on Employee Performance via Job Satisfaction at Ministry of Religious Affairs Jepara Office - Naiul Muna Amaliya; Asyhari Asyhari (eCo-Buss, 2025)
The decline in employee performance achievement at the Ministry of Religious Affairs Office of Jepara Regency in recent years indicates issues related to work-life balance and self-efficacy, which may affect job satisfaction and performance. This research seeks to examine how the balance between work and personal life, along with self-confidence, influences job performance, considering job satisfaction as a mediating factor. A quantitative method with an explanatory framework was used for the study. The population consisted of 138 employees, and a sample of 103 respondents was selected using purposive sampling. Information was gathered through a Likert-scale survey and examined using multiple linear regression and Sobel tests with the help of SPSS. The results show that work-life balance has a positive and significant effect on job satisfaction (β=0.329; p<0.05) and employee performance (β=0.241; p<0.05). Self-efficacy also has a positive and significant effect on job satisfaction (β=0.417; p<0.05) and employee performance (β=0.275; p<0.05). Furthermore, job satisfaction significantly influences employee performance (β=0.356; p<0.05) and mediates the relationship between work-life balance, self-efficacy, and performance. These results emphasize the significance of handling work-life balance and enhancing self-confidence to boost job satisfaction and employee effectiveness. The practical implication is that human resource management in government institutions needs to develop policies that support work-life balance and employee capacity-building programs to achieve sustainable performance improvement.